A new medium for remote music tuition. Issue 1 (1st May 2017) - Duffy, Sam; Healey, Patrick
It is common to learn to play an orchestral musical instrument through regular one-to-one lessons with an experienced musician as a tutor. Students may work with the same tutor for many years, meeting regularly to receive real-time, iterative feedback on their performance. However, musicians travel regularly to audition, teach and perform and this can sometimes make it difficult to maintain regular contact. In addition, an experienced tutor for a specific instrument or musical style may not be available locally. General instrumental tuition may not be available at all in geographically distributed communities. One solution is to use technology such as videoconference to facilitate a remote lesson; however, this fundamentally changes the teaching interaction. For example, as a result of the change in communication medium, the availability of non-verbal cues and perception of relative spatiality is reduced. We describe a study using video-ethnography, qualitative video analysis and conversation analysis to make a fine-grained examination of student–tutor interaction during five co-present and one video-mediated woodwind lesson. Our findings are used to propose an alternative technological solution – an interactive digital score. Rather than the face-to-face configuration enforced by videoconference, interacting through a shared digital score, augmented by visual representation of the social cues found to be commonly used in co-present lessons, will better support naturalistic student–tutor interaction during the remote lesson experience. Our findings may also be applicable to other fields where knowledge and practice of a physical skill sometimes need to be taught remotely, such as surgery or dentistry.